EVALUASI KINERJA DAS DAN SIMULASI KONSERVASI MENGGUNAKAN SWAT (SOIL AND WATER ASSESSMENT TOOL) (StudiKasus : Sub DAS Tapung, Siak, Provinsi Riau) - Mardan Fajri; Manyuk Fauzi; Ari Sandhyavitri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Alteration of land use which is happening at left Tapung watershed (DASTapungKiri) is effect to rate of flow of the watershed. Marked by the decreasing offorest area from 15.624,36 ha at 2002 to 12.186,32 ha at 2012. Evaluation ofwatershed condition and performance is needed. Evaluation using (i) Percentageof critical land (PLK) (ii) Percentage of vegetation cover (PPV) (iii) Coefficientregim of flow(KRA) (iv)Coannual of flow (KAT) efficient criteria. Evaluationresult of PLK is 9,82%, PPV 71,6%, KRA 14,28 and KAT 0,45. After receivingexisting evaluation value, conservation simulation using SWAT program is doneby changing a part of open land area and shrub on land use map of 2012 withforest. From simulation result, SWAT model validity parameter R2 is 0,50 andNSE 0,50. These result have satisfied the research objectives as the findingcoefficient were > R2 0,4 and >NSE 0,35 From this simulation, watershedcondition is evaluated again. Evaluation result after doing conservationsimulation are PLK 6,52 % PPV 73,08 % KRA 5,78, and KAT 0,44. Values afterconservation simulation gives better result than the condition before conservationsimulation is done.Keywords: altration of land use, SWAT, watershed performance.